Documents Clustering Using K-Means Algorithm - R.B Wahyu; Arnold Vito (President University, 2018)
Nowadays in the digital era, people could easily access and stored a wide range of information through the Internet into documents. With the huge number of unstructured documents with various type of information in digital storage, people need an application that could help them organize and classify the documents automatically. Documents Clustering using K-Means Algorithm is a desktop-based documents clustering application which implement K-Means Algorithm to provides clustering output based on the documents content similarity up to 85% accuracy based on the user expectation.